The Effect of Anxiety Towards the Academic Performance of Undergraduate Students in Public Universities in Malaysia - Liew, Yi Wen; Hamzah, Hazalizah; Mustapha, Roslinda (EDUCATUM Journal of Social Sciences, 2021)
This research is a survey to examine the effects of state/trait anxiety towards academic achievement among undergraduates. This study also examines the mediation effect of academic motivation in these relationships. Furthermore, it also investigates gender differences in state anxiety, trait anxiety, academic motivation, and academic performance among undergraduates of Malaysian public universities. Students. To achieve the purpose of study, 143 undergraduates from public universities in Malaysia were surveyed using State-Trait Anxiety Inventory, Demographic Questionnaire and Academic Motivation Scale-College version. The data for were analyzed using descriptive analysis, independent t-test, regression analysis and Sobel test by through SPSS version 23. This study indicated that there is no direct effect of state anxiety and trait anxiety on academic performance among undergraduates. However, they have indirect effects on undergraduates’ academic performance through academic motivation. Furthermore, gender difference was not found to be significant in this study in terms of all the variables involved. For the educational purpose, the influence of academic motivation among undergraduates should be taken into account by various parties such as education providers and policy makers in order to ensure a better academic outcome among undergraduates.